Fine-scale decomposition of China’s underdeveloped regional CO2 emissions peaking targets: a case study of Gansu Province - Yan Li; Qiaoliang Zhang; Taozhen Huang; Zhencheng Xing (Ecological Processes)
Abstract Background China’s national “Dual Carbon” goals have set clear timelines and imposed more stringent requirements for regional emission reductions. To effectively achieve these goals, developing an equitable carbon allocation framework at a finer, county-level scale is essential. This study develops a county-level carbon quota allocation scheme for peak emissions in Gansu Province—a representative underdeveloped region in western China. Grounded in the ‘equal cumulative per capita net emissions’ principle, the framework incorporates both cumulative carbon sources and sinks, aiming to ensure an equitable and fine allocation of carbon responsibilities. Results Our results indicate that Gansu’s total carbon emissions substantially exceed its carbon absorption capacity, with this gap widening over time. Spatially, carbon emissions and sinks exhibit contrasting regional distributions across the province, reflecting pronounced differences in population density, resource endowments, and industrial structures. Future projections suggest that Gansu’s emissions will continue to grow and are expected to peak at 214.6 Mt in 2030. At the county/district level, notable disparities exist in the carbon quotas for peak emissions, ranging from a deficit of − 7.4 Mt in Honggu to a surplus of 12.2 Mt in Chengguan. These variations underscore the critical need for county-level carbon allocation strategies. As a result, counties/districts in central Gansu face heightened pressures to reduce emissions, while those in the northern and southern areas have relatively larger emission allowances. Conclusions The allocation strategy based on cumulative net emissions not only protects the development rights of less developed counties/districts, thereby promoting regional equity, but also safeguards the interests of those with valuable ecosystems, such as Subei, Sunan, and Wen counties. Given the substantial disparities in emissions reduction pressures, capacities, and potentials across Gansu’s counties/districts, integrating the allocation scheme with a market-based carbon trading mechanism can facilitate cost-effective emissions reductions, thereby assisting Gansu in achieving its carbon peak.